Heat-shock protein 104 expression is sufficient for thermotolerance in yeast. - Lindquist, S (1996)
In all organisms, mild heat pretreatments induce tolerance to high temperatures. In the yeast Saccharomyces cerevisiae, such pretreatments strongly induce heat-shock protein (Hsp) 104, and hsp104 mutations greatly reduce high-temperature survival, indicating Hsp1O4 plays a critical role in induced thermotolerance. Surprisingly, however, a heat-shock transcription factor mutation (hsf1-m3) that blocks the induction of Hsps does not block induced thermotolerance. To resolve these apparent contradictions, we reexamined Hsp expression in hsf1-m3 cells. HsplO4 was expressed at a higher basal level in this strain than in other S. cerevisiae strains. Moreover, whereas the hsf1-m3 mutation completely blocked the induction of Hsp26 by heat, it did not block the induction of Hsp1O4. HSP104 could not be deleted in hsf1-m3 cells because the expression of heat-shock factor (and the viability of the strain) requires nonsense suppression mediated by the yeast prion [PSI+], which in turn depends upon Hsp1O4. To determine whether the level of Hsp1O4 expressed in hsf1-m3 cells is sufficient for thermotolerance, we used heterologous promoters to regulate Hsp1O4 expression in other strains. In the presence of other inducible factors (with a conditioning pretreatment), low levels of Hsp1O4 are sufficient to provide full thermotolerance. More remarkably, in the absence of other inducible factors (without a pretreatment), high levels of Hsp1O4 are sufficient. We conclude that Hsp1O4 plays a central role in ameliorating heat toxicity. Because Hsp1O4 is nontoxic and highly conserved, manipulating the expression of Hsp1OO proteins provides an excellent prospect for manipulating thermotolerance in other species.